Positive effect of 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) on homogeneous photocatalytic reduction of CO2. Issue 27 (8th February 2018) - Pschenitza, Markus; Meister, Simon; Rieger, Bernhard
Abstract : Addition of DBU enables reducing the amount of sacrificial electron donor and increases catalytic performance in photocatalytic CO2 reduction. Abstract : A significant decrease in the amount of the sacrificial electron donor triethanolamine (TEOA) required for the homogeneous photocatalytic reduction of CO2 using rhenium-based catalytic systems can be achieved by adding small quantities of 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) to the reaction mixture. The turnover numbers (TONs) and frequencies (TOFs) measured for the reactions described herein are even higher than those observed in reaction mixtures containing high concentrations of TEOA. Furthermore, replacing TEOA with DBU in the solutions of Re(i )/Ru(ii ) mixed catalytic systems leads to a doubling of the values of TON and TOF.